(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Introduction: Chromium [Cr (VI)] was considered as one of the most famous cytotoxic environmental pollutants. It was believed to be a health harmful agent in cumulative way. Natural Propolis was thought to possess anti-inflammatory, anti-cytotoxic, and antioxidant abilities. Objective: The purpose of this study was to assess Propolis' ability to protect rats' lungs from chromium-induced lung damage. Material and Methods: Four equal groups of twenty-four adult male albino rats were established: Group I: served as control received normal saline. Group II (Propolis group): treated with 50 mg/kg/day of Propolis orally through gastric tube for four weeks. Group III [Sodium Dichromate Cr (VI) group]: received sodium dichromate intraperitoneal (i.p.) over eight days, at dosages of 12 mg/kg every day. Group IV were pretreated with Propolis for four weeks before administration of Sodium Dichromate Cr (VI) for eight sequential days at previous mentioned doses. At the end of experiment the animals were sacrificed after anesthesia and their lungs were removed and processed for biochemical, histological, and immunohistochemical investigations. Results: Sodium dichromate Cr (VI) produced distortion of bronchial mucosa, inflammatory cellular infiltration, and congestion of blood vessels. Biochemical markers showed significant induction of malondialdehyde (MDA) levels indicating lipid peroxidation, significant decrease of glutathione (GSH) and superoxide dismutase (SOD) levels indicating oxidative effect in group III in contrast to the control group. The total area percentage of collagen fibers and the positive caspase-3 immunostained cells were significantly considerably higher in group III when compared to the control group. The administration of Propolis showed obvious improvement of these pulmonary alterations. Conclusion: Exposure to Cr (VI) induced lung intoxication in the form of structural changes of the lung tissue. Collectively, the present study suggested that Propolis allows pulmonary protection against the inflammation and apoptosis caused by Chromium.